The Influence of Leadership and Job Satisfaction on Police Performance at the South Kalimantan Regional Police - Bahagia Dachi; Oscarius Yudhi Ari Wijaya (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The Indonesian National Police (Polri) continues to encounter performance challenges; however, the specific influence of leadership and job satisfaction on officer performance within the South Kalimantan Regional Police has yet to be examined. The present inquiry seeks to elucidate the nexus between job satisfaction and the performance of Polri personnel, as well as the association between leadership and organizational performance. To ascertain the magnitude and direction of the effects of leadership and job satisfaction on performance, the study employed multiple linear regression techniques utilizing SPSS software. The methodological sequence comprised primary data collection through structured questionnaires, subsequent validity and reliability verification, classical assumption diagnostics, including assessments of multicollinearity, heteroscedasticity, and normality, followed by multiple regression modeling to estimate both partial effects (via t-statistics) and simultaneous effects (via F-statistics), and coefficient of determination (R²) analysis to evaluate the model’s explanatory capacity. The analytical framework adopted was Multiple Linear Regression Analysis, designed to reveal the relationship between leadership and job satisfaction towards police performance. The empirical sample consisted of 345 Polri officers stationed in South Kalimantan, selected through probabilistic random sampling procedures. Data were gathered through the distribution of Likert-type questionnaires, employing a five-point response continuum. The data screening process incorporated validity and reliability testing to ensure construct precision and internal consistency, alongside partial hypothesis testing using the t-test. The empirical evidence reveals that job satisfaction exerts a positive and statistically significant influence on Polri performance, while leadership similarly demonstrates a positive and significant contribution to performance enhancement.